PENGARUH SIFAT MACHIAVELLIAN DAN TIPE KEPRIBADIAN PADA PERILAKU DISFUNGSIONAL AUDITOR - Saputri, I G. Agung Yuli; Wirama, Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.02.TAHUN 2015, 2015)
In the context of audit, dysfunctional behavior is considered to be deviant behavior conducted by auditor in the process of audit. Dysfunctional behavior should be avoided by auditor since it affects the reliability of report which can consequently be detrimental to public interest. The tendency of dysfunctional behavior can be reduced by identifing some causal factors arising from the internal side of auditor. This research investigates the influence of Machiavellianism and type of personality on the dysfunctional behavior of auditor. In this study, data were collected through questionnaire. The population constitutes auditors who work on public account firms in Bali with total sample of 72 auditors obtained by saturated sampling methods. Data were analyzed using multiple linear regressions technique. The validity, reliability, and classical assumption test has been conducted prior to examining the hypothesis. The results of this study show that Machiavellianism and type of personality have significant effects on auditor dysfunctional behavior. Auditor with high Machiavellian values and type ‘A’ personality will tend to engage in dysfunctional behavior.
Keywords: Machiavellianism, type of personality, auditor dysfunctional behavior